Creation of the Seoul Brand through Hallyu - Rodríguez Castillo, Julia (2020)
This article focuses on the VisitSeoul.netactivities, as part of I.Seoul.U brand, to observe South Korea capital´s brand and understand how the Seoul Metropolitan Government has developed and develops different strategies and activities through its identity and image. From a documentary review and an in-depth interview with Lee Doo Ran (Seoul City Council), as well as an exploration that allows us to understand these activities, the importance of Hallyu (The Korean Wave) for the South Korean capital is investigated for understanding how the Seoul Metropolitan Government, using Hallyu, develops strategies and activities focused on maturing and respecting its city brand.